Comparison of the Dental Caries Experience and Some Salivary Physicochemical Variables among Iraqi Boxers - H Obied Majhool; A Ahmed Qasim (Majallah-i Dānishgāh-i ̒Ulūm-i Pizishkī-i Bābul)
Background and Objective: Due to the importance of oral hygiene to athletes in the evaluation of oral health status, efforts continue to raise their performance. This study aims to determine a correlation between some salivary physicochemical variables to dental caries in Iraqi boxers. Methods: This cross-sectional study was conducted on 80 people in two groups of 40, including 40 boxers in different boxing clubs in Baghdad and 40 male students aged 15-16 from different schools in Baghdad. The two groups were compared in terms of some variables including age, sex, education status, general health status. The clinical assessment of dental caries was done by dental mirror and dental probes. The unstimulated salivary analysis included samples collected to determine pH (measured by pH meter), flow rate (By dividing the measured amount of saliva by ml/min) and minerals like calcium (measured by calcium kit), and salivary immunoglobulin A (measured by ELISA kit). Findings: There were no significant differences between the two groups in terms of demographic variables. Dental caries was seen in the study group in 100% of 40 subjects compared to control group (2.5%). The mean value of decay surfaces, missing surfaces, decay missing filling teeth, and decay missing filling surfaces show high levels with a significant difference in the study group 20.275±6.880, 4.050±5.514, 11.775±3.779 and 24.450±9.375 respectively (p<0.05). The mean values to the pH and flow rate were 5.903±0.568, 0.939±0.445 respectively (p<0.05). For the salivary immunoglobulin A (IgA) and calcium, they were about 0.375±0.123, 0.887±0.260 respectively (p<0.05) and were lower in the study groups, indicating statistically significant differences. Conclusion: According to the result of this study, dental caries had a negative correlation with pH and flow rate. Also, salivary calcium and salivary IgA show a negative correlation with dental caries.